Glycocalyx Degradation Is Independent of Vascular Barrier Permeability Increase in Nontraumatic Hemorrhagic Shock in Rats. (August 2019) - Guerci, Philippe; Ergin, Bulent; Uz, Zuhre; Ince, Yasin; Westphal, Martin; Heger, Michal; Ince, Can
Abstract : BACKGROUND: Glycocalyx shedding after traumatic hemorrhagic or septic shock, as well as different resuscitation fluids, has been causally linked to increased vascular barrier permeability (VBP) resulting in tissue edema. In nontraumatic hemorrhagic shock (NTHS), it remains questionable whether glycocalyx degradation in itself results in an alteration of VBP. The composition of fluids can also have a modulatory effect on glycocalyx shedding and VBP. We hypothesized that the shedding of the glycocalyx during NTHS has little effect on VBP and that the composition of fluids can modulate these effects. METHODS: Fully instrumented Wistar-albino rats were subjected to a pressure-controlled NTHS (mean arterial pressure of 30 mm Hg) for 60 minutes. Animals were fluid resuscitated with Ringer's acetate, balanced hydroxyethyl starch (HES) solution, or 0.9% normal saline to a mean arterial pressure of 80 mm Hg and compared with shams or nonresuscitated NTHS. Glycocalyx shed products were determined at baseline and 60 minutes after fluid resuscitation. Skeletal muscle microcirculation was visualized using handheld vital microscopy. VBP changes were assessed using plasma decay of 3 fluorescent dyes (40- and 500-kDa dextran and 70-kDa albumin), Evans blue dye exclusion, intravital fluorescence microscopy, and determination of tissue edema (wet/dry weight ratio). RESULTS: All glycocalyx shedding products were upgraded as a result of NTHS. Syndecan-1 significantly increased in NTHS (mean difference, −1668; 95% confidence interval [CI], −2336 to −1001; P < .0001), balanced crystalloid (mean difference, −964.2; 95% CI, −1492 to −436.4; P = .0001), and HES (mean difference, −1030; 95% CI, −1594 to −465.8; P = .0001) groups at the end of the experiment compared to baseline. Hyaluronan levels were higher at the end of the experiment in nonresuscitated NTHS (−923.1; 95% CI, −1216 to −630; P = .0001) and balanced crystalloid (−1039; 95% CI, −1332 to −745.5; P = .0001) or HES (−394.2; 95% CI, −670.1 to −118.3; P = .0027) groups compared to controls. Glycocalyx shedding resulted in microcirculation alterations as observed by handheld video microscopy. Total vessel density was altered in the normal saline (mean difference, 4.092; 95% CI, 0.6195–7.564; P = .016) and hemorrhagic shock (mean difference, 5.022; 95% CI, 1.55–8.495; P = .0024) groups compared to the control group, as well as the perfused vessel density and mean flow index. Despite degradation of endothelial glycocalyx, VBP as determined by 4 independent assays remained intact and continued to be so following fluid resuscitation. CONCLUSIONS: NTHS induced glycocalyx shedding and microcirculation alterations, without altering VBP. Fluid resuscitation partially restored the microcirculation without altering VBP. These results challenge the concept that the glycocalyx barrier is a significant contributor to VBP.